METODE ISTINBATH DALAM USHUL FIQH STUDI KASUS : AYAT-AYAT EKONOMI - siti nailul izzah (Universitas Muhammadiyah Surabaya, 2021)
Method Istinbath is one of the methods of digging the law in ushul fiqh. Where the method of istinbath is used to draw the law from the Qur'an and Sunnah by way of ijtihad. Then this method is associated with economics which is a form of human responsibility as a caliph to create a balance in life to be maintained. The ever -growing economy makes Muslims need guidance in digging or establishing a law. The source of this method is from the arguments of the Qur'an and Sunnah which are seen in terms of language, in terms of the purpose (maqasid) of sharia and in terms of resolving conflicting arguments. In this research focuses onlaw through linguistic terms with the approach of lafadz (exploring thethuruq lafdziyah) and the approach of meaning (thuruq maknawiyah). The approach of lafadz (thuruq lafdiyah) is divided into 4 (four) types: lafadz seen from the scope or meaning created, lafadz seen from the side of use of meaning, lafadz seen from the clear side or not in showing a meaning, and lafadz seen from the way it expresses a meaning.